MASALAH MAFIA PERADILAN DAN KORUPSI DI INDONESIA - Wahyu Wiriadinata (Syiar Hukum, 2010)
The terminology mafia or Cosa Nostra derived from the Italian term with a negative sense that means an activity of organized crime networks.  Furthermore, the terminology of mafia in courts has been rose in Indonesia since the new order era and increasingly in the reform era.  Such terminology can be defined as an organized activity performs in court from the beginning stages of investigation until the investigation, prosecution and execution, either in criminal, civil, or state administration court.  In its activities, the Mafioso (people who act mafia in courts), often use an unlawful act such as bribery, by giving a gratuity, to the law enforcement officers on purpose to influence their decisions to fulfill the wishes of the Mafioso.  What such Mafioso done is an action of corruption. This research focuses on the problem of mafia in courts and corruption and its impact to the law enforcement purposes that are achieving legal certainty and justice in society, and some ways to combat them.